Cell‐free DNA screening for rare autosomal trisomies and segmental chromosome imbalances. (22nd September 2022) - Raymond, Yvette C.; Fernando, Shavi; Menezes, Melody; Meagher, Simon; Mol, Ben W.; McLennan, Andrew; Scott, Fergus; Mizia, Karen; Carey, Karen; Fleming, Gabrielle; Rolnik, Daniel Lorber
Abstract: Objective: To assess the outcomes of pregnancies at high‐risk for rare autosomal trisomies (RATs) and segmental imbalances (SIs) on cell‐free DNA (cfDNA) screening. Method: A retrospective study of women who underwent cfDNA screening between September 2019 and July 2021 at three ultrasound services in Australia. Positive predictive values (PPVs) were calculated using fetal chromosomal analysis. Results: Among 23, 857 women screened, there were 93 high‐risk results for RATs (0.39%) and 82 for SIs (0.34%). The PPVs were 3.8% (3/78, 95% CI 0.8%–10.8%) for RATs and 19.1% (13/68, 95% CI 10.6%–30.5%) for SIs. If fetuses with structural anomalies were also counted as true‐positive cases, the PPV for RATS increased to 8.5% (7/82, 95% CI 3.5%–16.8%). Among 85 discordant cases with birth outcomes available (65.4%), discordant positive RATs had a significantly higher proportion of infants born below the 10th and 3rd birthweight percentiles than expected (19.6% ( p  = 0.022) and 9.8% ( p  = 0.004), respectively), which was not observed in the SI group (2.9% < 10th ( p  = 0.168) and 0.0% <3rd ( p  = 0.305)). Conclusion: The PPVs for SI and RAT results are low, except when a structural abnormality is also present. Discordant positive RATs are associated with growth restriction. Key points: What is already known about this topic? Prenatal cell‐free DNA (cfDNA) screening has high accuracy in screening for trisomies 21, 18 and 13. The positive predictive values of cfDNA screening for rare autosomal. Trisomies rare autosomal trisomies (RATs) and segmental imbalances (SIs) are lower than that for common autosomal trisomies. Fetal exclusion of chromosomal anomaly following high‐risk cfDNA screen may indicate confined placental involvement. What does this study add? True‐positive (fetal) results are infrequent in women screened high‐risk for SIs and RATs in the absence of ultrasound findings. Discordant positive cfDNA results for RAT may indicate an increased risk of growth restriction. There does not appear to be any risk of growth restriction after a discordant positive SI result.